La littérature, la théorie et la critique sous contrainte. Notes sur le cas de l’Argentine (1966-1973/1976-1983) - Gerbaudo, Analía Isabel (2012)
This article is situated within a research that aims to generate an archive regarding the teaching methods developed by professors of Argentinean literature and literary theory in public universities in the years after the dictatorship, that is between 1984 and 2003.This project, entitled Canon, Theory, and Interventions of the Critical Theorist Professors in Argentinean Universities After the Dictatorship, is interested in literary and theoretical cannons, pedagogical and scientific productions; it is developed within the Scientific Research activities of CONICET (Argentina) and implies planning over several years. This article exposes certain aspects of the research I have conducted between 2006 and 2010 on the two dictatorships in Argentina, namely the situation of literature, literary theory and literary criticism, especially in public universities.